Knowledge Management Dimensions and Sustainable Competitive Advantage (SCA) of Deposit Money Banks: Mediating Role of Innovation - Sev, Joseph Teryima; Avanenge, Faajir; Ode, Egena; John, Emakwu; Sev, Sylvia Sewuese; Aidi, Paul (Journal of Management and Research, 2022)
The primary objective of the current research was to explore how the Knowledge Management (KM) processes of Deposit Money Banks (DMBs) in Makurdi Metropolis contribute to their Sustainable Competitive Advantage (SCA). Additionally, this study determined to evaluate how innovation helps the banks to retain their competitive advantage. A total of 265 valid samples were collected from a population of 14 DMBs and 933 respondents were selected from these DMBs. The data was analysed using Structural Equation Modelling (SEM). While testing the assumptions, hypotheses 1-3 supported the proposition that KM dimensions; acquisition (β=.32, p <.05), utilization (β=.26, p <.05), and storage (β=.24, p <.05) were directly related to SCA. No evidence was found for the full mediating role of innovation in relation to KM dimensions and SCA, as demonstrated by the data. However, innovation does play a role in certain aspects of KM by demonstrating that acquisition (β=.69, p <.05), utilisation (β=.21, p <.05), and storage (β=.18, p <.05) are positively associated with innovation in DMBs. The findings indicated that managers who responded to KM were more innovative. The importance of DMBs lies in the recognition that knowledge is not a simple concept. A commitment to new discoveries and to new understandings is not sufficient. Enterprises need to pursue knowledge that enables them to add value.